2012
DOI: 10.1890/10-2050.1
|View full text |Cite
|
Sign up to set email alerts
|

Can rare positive interactions become common when large carnivores consume livestock?

Abstract: Livestock populations in protected areas are viewed negatively because of their interaction with native ungulates through direct competition for food resources. However, livestock and native prey can also interact indirectly through their shared predator. Indirect interactions between two prey species occur when one prey modifies either the functional or numerical responses of a shared predator. This interaction is often manifested as negative effects (apparent competition) on one or both prey species through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…mobility, olfactory cues), as most probably exhibited here by wolf spider predators, is believed to be a more general precondition for alternative prey to result in positive indirect effects (e.g. Sabo & Power, ; Koss & Snyder, ; Owen‐Smith & Mills, ; Sundararaj et al, ) and may explain the indirect effect that we observed.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…mobility, olfactory cues), as most probably exhibited here by wolf spider predators, is believed to be a more general precondition for alternative prey to result in positive indirect effects (e.g. Sabo & Power, ; Koss & Snyder, ; Owen‐Smith & Mills, ; Sundararaj et al, ) and may explain the indirect effect that we observed.…”
Section: Discussionmentioning
confidence: 56%
“…Thus, if a predator eats two species with no preference for either prey, an increase in one species necessarily decreases predation rates on the second (Koss & Snyder, 2005). However, prey vary in their quality and one prey species may be more nutritious, easier to detect, capture, or handle (van Baalen et al, 2001;Sundararaj et al, 2012). For example, Finke and Denno (2003) found that visually hunting wolf spiders were more likely to capture easily detected mobile prey compared with more cryptic and sedentary prey.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical response is defined as the change in predator density as a function of prey density while functional response is the change in predator's intake rate as a function of prey density [30,31]. In the context of the conservation and management of large mammal populations, such indirect interactions have received little empirical investigation [32], let alone their policy implications.
Figure 1.Schematic representation of apparent competition and apparent facilitation between livestock and wild prey, mediated by a predator.
…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed the functional response in simple predator-prey systems, from parasites and hosts (Morales et al 2001;Flores et al 2010) to vertebrate species such as nocturnal birds (Boutin 1995), feral cats (Harper 2005), Asiatic lions (Sundararaj et al 2012), lynxes, coyotes and wolves (Dale et al 1994;O'Donoghue et al 1998;Cariappa et al 2011). Systems with multiple prey species provide the opportunity for prey switching by generalist carnivores, but this has seldom been studied, unlike single prey systems, and data have previously been too limited for such an assessment for cougars [Puma concolor (Linnaeus, 1771)]; Ruth & Murphy 2010).…”
Section: Introductionmentioning
confidence: 99%